Modelling and experimental investigation of engine performance and emissions fuelled with biodiesel produced from Australian Beauty Leaf Tree. (15th June 2015) - Hassan, N.M.S.; Rasul, M.G.; Harch, C.A.
Highlights: Compression ignition (CI) engine performance and emission testing using biodiesel. Biodiesel produced from Australian Beauty Leaf Tree (BLT) oil. Engine combustion model development using CFD program AVL Fire. Optimisation of engine performance and emissions using energy balance. New knowledge towards development of BLT biodiesel industry in Australia. Abstract: This study first experimentally investigates the performance and exhausts emissions of a compression ignition (CI) engine fuelled with biodiesel produced from Australian beauty leaf tree (BLT) oil and compares these results with that of petroleum diesel. Then, an engine combustion model is developed using computational fluid dynamics (CFD) software, AVL Fire, to predict the engine performance and emission of those biodiesels and petroleum diesel. Experiments were done according to ISO 8178 standard engine test procedure using B5 biodiesel (5% BLT blend), B10 (10% BLT blend) and petroleum diesel in a 4-cylinder engine test-bed equipped with necessary dynamometer and sensors. The measurements were done for engine power, torque, specific fuel consumption and engine emissions. The combustion model is validated with the experimentally measured data, which shows very good agreement between them, more specifically variation of only up to 4.4% in power, 4.0% in torque and 3.3% in specific fuel consumption was found. The experimental results show that overall B10 biodiesel provides significantly reduced engine emissions, up to 18% compared to petroleum diesel. The validated model is then used to optimise the engine performance and emissions as a function of operating parameters such as ignition timing, crank angles and compression ratios. The simulation results show that B10 provides a slight improvement in performance and significant reduction in emission. It is believed that this paper provides a solid base of new knowledge towards achieving a sustainable BLT biodiesel industry.